A Retrospective Analysis of Therapists' Coaching Behavior When Directing Parents to Conduct Behavioral Assessments and Treatments Via Telehealth. Issue 1 (January 2023) - Larsen, Alesia; Schieltz, Kelly M.; Barrett, Amanda; O'Brien, Matthew J.
Research on the delivery of behavioral assessment and treatment via telehealth has focused largely on child outcomes and parent procedural fidelity. By contrast, the behavior of the therapists coaching parents to conduct assessment and treatment has garnered little research consideration. In this study, we conducted a retrospective analysis of behavior therapists' coaching behaviors when directing parents to conduct functional analysis (FA) and functional communication training (FCT) with their young children with autism via telehealth. Coaching behaviors for five experienced behavior therapists across seven parent-child dyads were scored using a combination of standardized and novel behavior codes. Therapists displayed more social engagement behaviors than any other type of behavior throughout the study, and rates of antecedent and consequence behaviors shifted across the FA and FCT phases. Results are discussed in relation to therapists' goals during behavioral assessment and treatment and the implications for training behavioral therapists to coach parents via telehealth.